1982
DOI: 10.1073/pnas.79.1.175
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in macrophage antigen catabolism caused by ammonia and chloroquine is associated with inhibition of antigen presentation to T cells.

Abstract: This paper describes the effects of two lysosomotropic compounds, ammonia and chloroquine, on the interaction of mononuclear phagocytes with immune T cells. The uptake and ingestion of Listeria monocytogenes by macrophages were not affected by the drugs; however, the macrophage catabolism of 'i5I-labeled Listeria was reduced in a dose-dependent way. The macrophage presentation ofListeria to T cells, an I-region-dependent phenomenon, was also inhibited. The degree of inhibition of catabolism paralleled that of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
233
0
1

Year Published

1987
1987
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 501 publications
(245 citation statements)
references
References 23 publications
11
233
0
1
Order By: Relevance
“…Rather, a continuous sensitization was noticed. This could be due to the requirement of accessory cells (macrophages) for catabolising the T cell-depending antigen and its presentation to T cells (28). Chloroquine neutralizes the pH of endosomes and prevents the recycling of the surface receptors of macrophages responsible for the presentation of antigen to T cells (29).…”
Section: Discussionmentioning
confidence: 99%
“…Rather, a continuous sensitization was noticed. This could be due to the requirement of accessory cells (macrophages) for catabolising the T cell-depending antigen and its presentation to T cells (28). Chloroquine neutralizes the pH of endosomes and prevents the recycling of the surface receptors of macrophages responsible for the presentation of antigen to T cells (29).…”
Section: Discussionmentioning
confidence: 99%
“…Lysosomal proteases introduce cleavages in endocytosed antigens, which trigger unfolding and capture of processed antigen by newly synthesised class II MHC molecules [8][9][10]. In addition, removal of the invariant chain (Ii) chaperone requires the action of one or more lysosomal proteases [11,12].…”
Section: Antigen Processing and Presentationmentioning
confidence: 99%
“…Ag processing required metabolically active macrophages but not protein synthesis. A subsequent study by these same authors reported that Ag processing required acidic intracellular vesicles, thereby establishing that the endosomal/lysosomal pathway was involved (9). Fixation of the macrophages with paraformaldehyde at various points after exposure to Listeria allowed a dramatic demonstration of the kinetics of Ag processing.…”
Section: Making Antigen Presentablementioning
confidence: 97%